Comprehensive Analysis of Expression Regulation for RNA m6A Regulators With Clinical Significance in Human Cancers - Liu, Xiaonan; Wang, Pei; Teng, Xufei; Zhang, Zhang; Song, Shuhui (Frontiers in Oncology, 2021)
Background: N6-methyladenosine (m6A), the most abundant chemical modification on eukaryotic messenger RNA (mRNA), is modulated by three class of regulators namely “writers”, “erasers”, and “readers”. Increasing evidence showed that RNA m6A modification plays an essential role in cancer development and aberrant expression of m6A regulators can affect tumor progression and metastasis. However, it is largely unknown regarding the expression regulation for RNA m6A regulators in human cancers. Results: Here we characterized the variation in expression profile of RNA m6A regulators in 13 cancer types from The Cancer Genome Atlas (TCGA), revealing that METTL14, FTO, and ALKBH5 were down-regulated in most cancer types, whereas YTHDF1 and IGF2BP3 were up-regulated in 12 cancer types except for thyroid carcinoma (THCA). Survival analysis with clinical information further revealed that high expression of several m6A regulators was correlated with the poor prognosis of patients in different cancers. Then, we analyzed microRNA (miRNA)-regulated and DNA methylation-regulated expression changes of m6A regulators in pan-cancer. In total, we identified 150 miRNAs and 58 DNA methylation probes (DMPs) involved in expression regulation for RNA m6A regulators in pan-cancer. Furthermore, we assessed the survival significance of those regulatory pairs. Among them, 10 miRNAs and 7 DMPs may promote cancer pathogenesis and progression; conversely, 3 miRNA/mRNA pairs in kidney renal clear cell carcinoma (KIRC) act as tumor suppressors, suggesting their potential as prognostic biomarkers. To evaluate the potential clinical application for those regulatory pairs, we validated two key miRNA/mRNA pairs (hsa-mir-18a/EIF3A and hsa-mir-304/IGF2BP3) in KIRC patients and found that these two pairs could well evaluate the survival of patients. Conclusions: Our findings highlighted the importance of upstream molecules (miRNAs and DNA methylation) governing m6A regulators’ expression in pan-cancer, and identified several regulatory pairs informative for prognostic stratification, which provide new insights into molecular mechanisms of m6A modification in human cancers.